2022
DOI: 10.3390/healthcare10112210
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Antibiogram of Acinetobacter baumannii Clinical Isolates Recovered from the Patients with Ventilator-Associated Pneumonia

Abstract: A 2-year prospective study carried out on ventilator-associated pneumonia (VAP) patients in the intensive care unit at a tertiary care hospital, Hail, Kingdom of Saudi Arabia (KSA), revealed a high prevalence of extremely drug-resistant (XDR) Acinetobacter baumannii. About a 9% increase in the incidence rate of A. baumannii occurred in the VAP patients between 2019 and 2020 (21.4% to 30.7%). In 2019, the isolates were positive for IMP-1 and VIM-2 (31.1% and 25.7%, respectively) as detected by PCR. In compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…These MDR pathogens are increasing the burden on the healthcare systems due to nosocomial infections in the ICU settings. [34][35][36] Our study showed that P. aeruginosa and A. baumannii produced three types of beta-lactamases, including MBL, ESBL, and AmpC. In contrast, K. pneumoniae isolates did not produce MBL.…”
mentioning
confidence: 67%
“…These MDR pathogens are increasing the burden on the healthcare systems due to nosocomial infections in the ICU settings. [34][35][36] Our study showed that P. aeruginosa and A. baumannii produced three types of beta-lactamases, including MBL, ESBL, and AmpC. In contrast, K. pneumoniae isolates did not produce MBL.…”
mentioning
confidence: 67%
“…The prevalence of ventilator-associated pneumonia (VAP) in Saudi Arabia is a significant concern, as it is one of the most common healthcare-associated infections in the country. The variation in the prevalence of the VAP found among prospective and retrospective studies is likely due to the selection criteria of the healthcare setting and patient population [34,39,43]. Most of the studies included patients with VAP only.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of resistance to cephalosporins in Saudi Arabia ranges from 9-98% [24,47]. However, the majority of the strains are susceptible to colistin [34,45,51]. Current data on antibiotic resistance and susceptibility patterns is insufficient, and there are calls for more comprehensive studies to be conducted, including testing for atypical pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations